Goal Scoring in Soccer: A Polar Coordinate Analysis of Motor Skills Used by Lionel Messi - Castañer, Marta; Barreira, Daniel; Camerino, Oleguer; Anguera, M. Teresa; Canton, Albert; Hileno, Raúl (Frontiers in Psychology, 2016)
Soccer research has traditionally focused on technical and tactical aspects of team play, but few studies have analyzed motor skills in individual actions, such as goal scoring. The objective of this study was to investigate how Lionel Messi, one of the world’s top soccer players, uses his motor skills and laterality in individual attacking actions resulting in a goal. We analyzed 103 goals scored by Messi between over a decade in three competitions: La Liga (n = 74), Copa del Rey (n = 8), and the UEFA Champions League (n = 21). We used an ad hoc observation instrument (OSMOS-soccer player) comprising 10 criteria and 50 categories; polar coordinate analysis, a powerful data reduction technique, revealed significant associations for body part and orientation, foot contact zone, turn direction, and locomotion. No significant associations were observed for pitch area or interaction with opponents. Our analysis confirms significant associations between different aspects of motor skill use by Messi immediately before scoring, namely use of lower limbs, foot contact zones, turn direction, use of wings, and orientation of body to move towards the goal. Studies of motor skills in soccer could shed light on the qualities that make certain players unique.